Sailing Beyond The Gate: Marketing Strategy And Positioning Of Marinor Cafe In A Campus-Bounded Market - Sandira, Nur Fadilah Ayu; Sarah, Nulthazam; Nasir, Sri Astuti; Iswardhani, Indri (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the marketing and positioning strategies implemented by Marinor Café in attracting consumers outside the Makassar Maritime Polytechnic (PIP) student environment. Marinor Café is a seafaring-themed culinary business unit located within the PIP Makassar campus area and has been operating since 2020. This study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that Marinor Café's marketing strategy still focuses on product aspects, prices, and interior design, while digital promotion aspects have not been optimally utilized. In addition, the café's positioning is not strong among off-campus consumers due to access barriers and minimal promotion. A SWOT analysis identified that although the café has advantages in thematic concepts and comfortable atmosphere, location barriers and lack of digital exposure are the main challenges. This study concludes that digital promotion optimization, market expansion, and positioning strengthening are needed so that Marinor Café can reach consumers more widely and sustainably.